Weimar surfaces : urban visual culture in 1920s Germany - Ward, Janet, 1963- (Berkeley : University of California Press, 2001)
This study revisits Weimar Germany via the lens of metropolitan visual culture, analyzing the power that 1920s Germany holds for today's visual codes of consumerism.
Introduction: Modern Surface and Postmodern Simulation: A Retrospective Retrieval 1. Functionalist Façades: The Reformation of Weimar Architecture 2. Electric Stimulations: The Shock of the New Objectivity in Weimar Advertising 3. Into the Mouth of the Moloch: Weimar Surface Culture Goes to the Movies 4. The Display Window: Designs and Desires of Weimar Consumerism.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Arts, German -- 20th century; Modernism (Aesthetics) -- Germany; Popular culture -- Germany -- Influence; Germany -- History -- 1918-1933.; Arts allemands -- 20e siècle.; Modernisme (Esthétique) -- Allemagne; Culture populaire -- Allemagne -- Influence; Allemagne -- Histoire -- 1918-1933.; ART -- Popular Culture; ARCHITECTURE -- History -- General; Arts, German; Modernism (Aesthetics); Popular culture -- Influence; Germany; 1900-1999; Humaniora -- Film; Humaniora -- Kunst; Samfundsvidenskab -- Sociologi; History